Comparing child wealth inequality across countries - Pfeffer, Fabian; Waitkus, Nora (RSF, 2021)
This article compares the wealth situation of children across fourteen countries. Children experience lower levels of wealth than the rest of the population, seniors in particular. We show that, in most countries, child wealth is distributed substantially more unequally than the wealth of seniors. We also demonstrate that an international ranking of child wealth inequality diverges sharply from one based on child income inequality. The wealth situation of children in the United States is exceptional: they lag further behind seniors in terms of their wealth and face the highest levels of wealth inequality and, by far, wealth concentration.
Gesehen am 16.05.2025